A Digital Storytelling Workshop with Mathematics Teachers - Ruhşen Aldemir Engin (e-Kafkas Eğitim Araştırmaları Dergisi, 2023)
This study presents reflections from an online Digital Storytelling Workshop conducted with mathematics teachers. In the study, which was designed as a qualitative case study, the participants comprised four people studying for a master’s degree at a state university in Turkey and who also worked as mathematics teachers in secondary schools. Data were collected through online lesson recordings, a semi-structured interview form, participants’ reflective diaries, and digital stories prepared during the process. Content analysis was used in the analysis of the data. According to the results of the research, it was determined that the participants had the most difficulty in creating a dramatic question and adding multimedia. It was seen that they paid more attention to the dramatic question, sound, and music elements while evaluating sample digital stories. They mentioned time-saving in terms of the advantages of holding the workshop online, and the fact that interaction was limited regarding the disadvantages. They stated that the workshop mostly benefited them in terms of technology. They reported that due to the disruptions experienced in online education, they used the prepared digital stories limitedly in their own classrooms, and stated they could not receive sufficient feedback. They also stated that in the event that they could use digital stories in mathematics classes, they would benefit students in various ways. The digital stories prepared at the end of the workshop were examined, and it was seen that there was an improvement in all participants